EFFECTS OF THE APPLICATION OF AN EDUCATIONAL INTERVENTION PROGRAM ON GROSS MOTOR SKILLS IN INDIVIDUALS WITH AUTISM - Astorino, Francisco; Contini, Liliana; Fessia, Gabriel; Manni, Diego (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2018)
Introduction: Autism is a neurodevelopment disorder called Autism Spectrum Disorder (ASD); it manifests in childhood, and it is characterized by limitations in social interactions and stereotyped behaviors. Objective: to evaluate the gross motor skills (GMS) development through a systematic program of general exercises in four adolescents with ASD. Methodology: conducting a longitudinal case study with two cross-sections; four adolescents aged 12 to14 years participated in a systematic education intervention program oriented to develop gross motor skills in twelve weeks (45-minute interventions, twice a week, one student per teacher). Before and after the systematic education intervention program to develop gross motor skills, the evaluation of students was made with the Assessment of Basic Language and Learning Skills (ABLL – R) score system. Results: after the intervention, the participants presented a positive result in improving physical activities compared to their results before the intervention. The most significant difficulty was in the activities of losing balance followed by a dynamic recovery, with or without objects. At the beginning of the intervention, all the participants presented deficiencies of gross motor skills. After the intervention, they showed an improvement in those skills. Conclusions: although people with ASD have permanent disabilities, the physical activity educationally oriented to adolescents ASD allowed significant progress in gross motor skills.